Legitimacy in EU Cartel Control. - Simonsson, Ingeborg (Modern studies in European law, 2010)
This book examines the law developed by the EU to control cartels. The law, including case-law, is carefully documented and analysed against a standard oflegitimacy which questions the EU's enforcement measures, its institutional structures, policy choices, substantive law, evidentiary standards and procedures and sanctions. It includes a unique catalogue of over 150 EU cartel decisions, as well as novel analyses of difficult borderline issues such as mixed horizontal and vertical cartels, single-brand dealer cartels and buyer cartels. The effect on trade in cartel cases is analysed with refer.